Spiritual Well-being and Attitude toward Spirituality and Spiritual Care in Nursing and Midwifery Students - N Rahimi; E Nouhi; N Nakhaee (Iran University of Medical Sciences, 2013)
Abstract   Background & Aims: The nursing and midwifery students are more spiritual health, better care and interventions for their patients are doing. The present study has been carried out in order to investigate the spiritual well-being and the attitude toward spirituality and spiritual care in nursing and midwifery students of Kerman University of Medical Sciences during 2012.   Material & Methods: This was a cross-sectional study. The population consisted of 222 students of nursing and midwifery studying in Kerman University of Medical Sciences, all of which were chosen as the sample of the study. Palutzian & Ellison questionnaire of spiritual well-being and ( SSCRS ( questionnaire of attitude toward spirituality and spiritual care was used to gather the data. The obtained data were then analyzed through SPSS 20 software using parametric statistical tests such as independent T-test, Anova test and Pearson correlation coefficient.   Re sults: Results showed the average of spiritual well-being and the attitude toward spirituality and spiritual care of nursing and midwifery students was in the good range (93/01 ± 13/78, 57/57 ± 10/70). the except Gener, No significant relationship was statistically observed between the mean of spiritual well-being and another parameters such as age, marital status, academic year, field of study and trainings in spirituality. And except age, No significant relationship was statistically observed between the mean of attitude toward spirituality and spiritual care and another parameters such as, Gener, marital status, academic year, trainings in spirituality, and field of study. (p=0/004,p=0/029) Between two variables, spiritual well-being and attitudes toward spirituality and spiritual care was found to be positively correlate.(p<0/001 )   Conclusion: According to the findings of spiritual health nursing and midwifery students was moderate The significance of these results to address the issue of spirituality in nursing and midwifery students show. It is necessary to promote spirituality and nursing and midwifery students planning to take place.   Received: 8 Oct 2013   Accepted: 25 Dec 2013